GAMBARAN PENGETAHUAN IBU DALAM MELAKUKAN PERTOLONGAN PERTAMA PADA KEJADIAN CEDERA PADA ANAK BALITA - Restu, Restu (Jurnal Keperawatan Profesional, 2024)
Incidents of injuries can occur in children under five which cause emergency conditions and are life threatening. This condition really requires the knowledge of mothers who understand how they can help their children at home. The purpose of this study is to describe the mother's knowledge about the management of first aid for injuries to children under five. Research using descriptive design. Using a purposive sampling technique, the number of samples in this study was 110. The results showed that the majority of respondents were aged 26-35 years, namely 44.5%, most of the respondents had high school education, namely 39.1%, with the majority working as housewives 63.6%. The majority of the respondent's religion is Islam 84.5%, and the majority of the population comes from the Malay ethnic group 34.5%. Mother's knowledge shows that most have good knowledge about first aid 57.3%. Mothers have good knowledge in helping children with injuries. However, an understanding of first aid procedures for injuries needs to be mastered by mothers in order to reduce the risk of complications of injury, even death in children under five, especially knowledge of first aid for poisoning injuries, nosebleeds and falls.